Error Analysis on the Use of Subordinating Conjunction Found in the Students’ Essay Writing at STKIP PGRI Sidoarjo - Hidayatul Murtafi’ah (P-SEMART JOURNAL, 2022)
Error analysis is a systematic method to analyze learners’ error in applying linguistics as well as a second and a foreign language. Subordinating conjunction is a conjunction that joins an independent clause and a dependent clause and also introduces adverb clauses. Investigating of error analysis through the students’ work is essential research as its aim. This study was conducted by the aims to describe the types of error found in the students’ essay writing and the most committed error based on the surface strategy taxonomy made by the 2nd semester students at STKIP PGRI Sidoarjo. Descriptive qualitative method was applied in conducting this study. The subjects of this study were the 2nd semester students at STKIP PGRI Sidoarjo. The instruments of this research were the researcher, documentation and table. The result showed that there were four types of errors found in the students’ essay writing based on the Surface Strategy Taxonomy called: (1) omission consisting 9 errors (29.03%), (2) addition consisting 2 times (6.45%), (3) misformation consisting 6errors (19.36%) and (4) misordering consisting 14errors (45.16%). Meanwhile, the most type of error was in the form of misformation error found 14 times (45.16%). However, the researcher addresses recommendations to 1) English teachers should be aware on grammatical errors in essay writing, 2) students to explore their writing ability to moderate errors, 3) other researchers to explore the implementation of error analysis in writing.